Coding Freedom : The Ethics and Aesthetics of Hacking - Coleman, E. Gabriella, 1973- (Book collections on Project MUSE., 2013)
Who are computer hackers? What is free software? And what does the emergence of a community dedicated to the production of free and open source software--and to hacking as a technical, aesthetic, and moral project--reveal about the values of contemporary liberalism? Exploring the rise and political significance of the free and open source software (F/OSS) movement in the United States and Europe, Coding Freedom details the ethics behind hackers' devotion to F/OSS, the social codes that guide its production, and the political struggles through which hackers question the scope and direction o.